Key terms of the Qurʾan a critical dictionary - Sinai, Nicolai 1976- (Princeton University Press, 2023)
"A one-volume, single-authored reference book featuring scholarly essays on key terms that appear in the Qur'an"--
Literaturverzeichnis Seite 737-767
Keywords: Koran; Terminologie; Qurʼan / Dictionaries; Qurʼan / Terminology; Qurʼan / Language, style / Terminology; Islam / Terminology; Wörterbuch